ANALISIS CELAH ENERGI OPTIK NANOROD ZINC OXIDE YANG DITUMBUHKAN PADA ZINC FOIL MENGGUNAKAN TEKNIK HIDROTERMAL - Anindita Prameswari Safitri; Adinda Salsabila Khansa; Nurfina Yudasari; Iwan Sugihartono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2026)
This study reports the synthesis and optical characterization of zinc oxide (ZnO) nanorods grown on zinc foil substrates via the hydrothermal method. The objective is to investigate the effect of growth duration on the morphology and optical band gap of ZnO. The synthesis was conducted at 95 °C for 4, 8, 12, 16, 20, and 24 hours, using Zn foil as both the substrate and Zn²⁺ source. Characterizations were performed using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and UV-Vis Diffuse Reflectance Spectroscopy (DRS). The results show that all samples exhibit a wurtzite crystal structure with a dominant (002) orientation. The nanorod morphology becomes denser and more uniform at growth durations of 12–24 hours. The band gap increased from 3.11 eV to 3.24 eV, with stable values observed between 12 and 24 hours. Therefore, hydrothermal growth time influences the structural and optical properties of ZnO, with 16–24 hours identified as the optimal duration for optoelectronic applications.